The Role of the Teacher in Enhancing the Effectiveness of Inclusive Education for Students with Special Needs in Mainstream Schools (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the role of teachers in enhancing the effectiveness of inclusive education for students with special needs in mainstream schools from the perspective of special education teachers at the primary school level under the Sabratha Education Office. The study adopted the descriptive-analytical approach due to its suitability for the nature and objectives of the research. The study population and sample consisted of all special education teachers working in primary schools affiliated with the Sabratha Education Office, totaling (20) teachers, who were selected using a purposive sampling method, To collect data, the researcher developed a questionnaire consisting of four main dimensions: planning and instruction, classroom management and learning environment, social interaction and psychological support, and collaboration with families and specialists. The validity of the instrument was established through expert review, while its reliability was verified using Cronbach’s Alpha coefficient. The findings revealed that the overall role of teachers in enhancing the effectiveness of inclusive education was rated very high, with an overall mean score of (4.27) out of (5). The dimension of social interaction and psychological support ranked first, with a mean score of (4.41), followed by classroom management and learning environment (4.33), planning and instruction (4.27), and collaboration with families and specialists (4.08), which ranked last despite remaining at a high level. The study recommended the development of professional training programs for teachers in the field of inclusive education, the provision of educational resources and assistive technologies, and the strengthening of cooperation among schools, families, and specialists. Such measures would contribute to improving the effectiveness of inclusive education programs and achieving their educational objectives.
Keywords: Inclusive Education, Teacher Role, Students with Special Needs, Mainstream Schools, Special Education, Inclusive Schooling.